Greenhouse gas emissions from Silphium perfoliatum and silage maize cropping on Stagnosols. Issue 1 (23rd November 2022) - Kemmann, Björn; Ruf, Thorsten; Well, Reinhard; Emmerling, Christoph; Fuß, Roland
Abstract: Background: The sustainability of bioenergy is strongly affected by direct field‐derived greenhouse gas (GHG) emissions and indirect emissions form land‐use change. Marginal land in low mountain ranges is suitable for feedstock production due to small impact on indirect land‐use change. However, these sites are vulnerable to high N2 O emissions because of their fine soil texture and hydrology. Aims: The perennial cup plant ( Silphium perfoliatum L.) might outperform silage maize ( Zea mays L.) on cold, wet low mountain ranges sites regarding yield and ecosystem services. The aim of this study was to assess whether the cultivation of cup plant also provides GHG mitigation potential compared to the cultivation of maize. Methods: A t‐year field experiment was conducted in a low mountain range region in western Germany to compare area and yield‐scaled GHG emissions from cup plant and maize fields. GHG emissions were quantified using the closed chamber method. Results: Cup plant fields emitted an average of 3.6 ± 4.3 kg N2 O‐N ha –1 year –1 (–85%) less than maize fields. This corresponded to 74.0 ± 94.1 g CO2‐eq kWh –1 (–78%) less emissions per produced electrical power. However, cup plant had a significantly lower productivity per hectare (–34%) and per unit of applied nitrogen (–32%) than maize. Conclusion: Cup plant as a feedstock reduces direct field‐derived GHG emissions compared to maize but, due to lower yields cup plant, likely increases emissions associated with land‐use changes. Therefore, the increased sustainability of bioenergy from biogas by replacing maize with cup plant is heavily dependent on the performance of maize at these sites and on the ecosystem services of cup plant in addition to GHG savings.